Exotic superconducting states in the extended attractive Hubbard model. (2nd March 2018) - Nayak, Swagatam; Kumar, Sanjeev
Abstract: We show that the extended attractive Hubbard model on a square lattice allows for a variety of superconducting phases, including exotic mixed-symmetry phases with d x 2 − y 2 + i [ s + s ∗ ] and d x 2 − y 2 + p x symmetries, and a novel p x + i p y state. The calculations are performed within the Hartree–Fock Bardeen–Cooper–Schrieffer framework. The ground states of the mean-field Hamiltonian are obtained via a minimization scheme that relaxes the symmetry constraints on the superconducting solutions, hence allowing for a mixing of s -, p - and d -wave order parameters. The results are obtained within the assumption of uniform-density states. Our results show that extended attractive Hubbard model can serve as an effective model for investigating properties of exotic superconductors.